A bibliometric analysis of the Journal of Membrane Science (1976-2010). Issue 4 (3rd August 2015) - Fu, Hui-Zhen; Ho, Yuh-Shan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to examine publication characteristics and development of a science journal Journal of Membrane Science (JMS) with 35 years ' history by bibliometric indicators. Design/methodology/approach – A bibliometric approach was used to identify its document types, impact factor, publication outputs, most cited articles and large contributing countries/territories and institutions. The main indicators included impact factor, CPP (citations per publication), TC2010 (number of citations from one paper's publication to the end of 2010), C2010 (number of citations in the year of 2010), number of total articles, "single country articles" and "single institution articles", "internationally collaborative articles" and "inter-institutionally collaborative articles", "first author articles" and "corresponding author articles". The annual citations of most cited articles were displayed in a table list. Findings – The two-year citation window used by impact factor is not fair for a journal which had its peak annual citations in the third or more years. JMS would get a better citation performance if impact factor can be calculated for three or four years. Impact factor is affected by the size of its subject categories. JMS showed higher impact factor rankings in both chemical engineering and polymer science category in the early twenty-first century. Furthermore, the G8 (Canada, France, Germany, Italy, Japan, Russia, the UK and the USA) contributed more than a half of the total, with higher CPP. National University of Singapore, University of Twente and Chinese Academy of Sciences were the main contributing institutions. The citation life cycles revealed the impact history of most cited articles. Originality/value – A bibliometric analysis has been carried out to analyze the characteristics of a journal with 35 years ' history. Some improved indicators including TC2010, C2010, TP, SP, CP, FP and RP have been used for the evaluation. This study provides an evidence from JMS to discuss the feasibility and limitations of impact factor.